Epidemiology of filariasis malayi in Muara Padang Village, Muara Padang SubDistrict, Banyuasin District, South Sumatra, Indonesia - Erwin Edyansyah Soeyoko Sri Sumarni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Filariasis is still a public health problem in Indonesia especially in rural areas. In South SumatraProvince, 186 patients with chronic filariasis were reported in 2009 and 130 of them came fromBanyuasin District. In Muara Padang SubDistrict, there were 7 patients with chronic filariasisand 1 of them lived in Muara Padang Village. A finger blood survey has never been conducted inMuara Padang Village since elimination program started in 2002. The aim of the study was toevaluate epidemiology of filariasis malayi in the Muara Padang Village. This was a descriptivestudy using cross sectional design. Data were collected from finger blood survey, blood tests forreservoir host (cats), stage 3 of filarial larvae (L3) in mosquito and microfilaria periodicityexamination. From 520 finger blood samples collected from the inhabitants, microfilaria was notobserved. However, 1 subject was found to have elephantiasis caused by filariasis malayi asindicated by swelling leg below the knee. Moreover, 1 subject showed descending lymphangitissymptoms accompanied by fever, headache and weakness even though in blood examinationmicrofilaria was not found. Among 17 samples collected from cats, microfilaria of Brugia malayiwas not observed. However, animal filarial i.e. Dirofilaria repens was observed in 11 samplescollected. Among 701 mosquitoes dissection and examination, L3 was not found. Due to thefact that the microfilaria was not observed in all samples, microfilaria periodicity examinationwas not conducted. In conclusion, microfilaria of B. malayi was not observed in Muara PadangVillage. However, microfilaria of D. repens was observed in cats.